PENGARUH MEKANISME GOOD CORPORATE GOVERNANCE, REPUTASI KAP DAN UKURAN PERUSAHAAN TERHADAP KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN PADA PERUSAHAAN PERDAGANGAN, JASA DAN INVESTASI TAHUN 2018 – 2020 - Alya Rahayu Taufiq; Azwirman (Jurnal Ekonomi KIAT, 2023)
The purpose of this study is to evaluate and analyze the following : (1) the effect of mechanism of good corporate governance on the timeliness submission of financial report , (2) the effect of reputation of public accountant firm on the timeliness submission of financial report, (3) the effect of company size on the timeliness submission of financial report. The population in this study were Trading, Service and Investment Company listed on the Indonesian Stock Exchange (IDX) in 2018 – 2020. In this study, using a purposive sampling technique. The results showed that the audit committee, independent commissioners and reputation of public accountant firm had a significant effect on the timeliness submissing of financial report. Meanwhile, institutional ownership, managerial ownership, and company size have no significant effect on the timeliness submissing of financial report.